Depressive Symptoms (Not Type D Personality) Predict Quality of Life in Survivors of Differentiated Thyroid Cancer. (29th July 2020) - Wiener, Chelsea H.; Deavers, Frances; Cassisi, Jeffrey E.; Husson, Olga; Fleurestil, Sarah
Objective: Survivors of differentiated thyroid cancer (DTC) report impaired quality of life despite long duration of cure. Research regarding predictors of quality of life in this population has largely been limited to demographic characteristics. Type D personality (high levels of negative affect and social inhibition) is correlated with quality of life in other chronic illness populations, but has not been thoroughly assessed in survivors of DTC. Therefore, the present study assessed Type D personality as a predictor of quality of life in survivors of DTC. Depressive symptoms were controlled for in analyses to address concerns regarding conceptual similarity of Type D personality to depression. Methods: Participants included survivors of DTC as registered in the Patient Reported Outcomes Following Initial Treatment and Long-term Survivorship (PROFILES) registry. Questionnaires on psychosocial functioning were mailed to 334 survivors. Data from eligible respondents ( N = 284) were utilized in logistic regressions to assess relationships between Type D personality and quality of life domains. Results: Type D personality did not predict physical, social, cognitive, or role functioning beyond what was predicted by depression. Type D personality did add to the prediction of impairment in emotional functioning at the .01 alpha level. Depression significantly predicted impaired quality of life across all measured domains. These findings were replicated across categorical and continuous measurement approaches. Conclusions: Depressive symptoms robustly predict quality of life in survivors of DTC. Type D personality does not predict quality of life beyond what is accounted for by symptoms of depression in most quality of life domains.